Ligand-mediated Structural Dynamics of a Mammalian Pancreatic KATP Channel. Issue 19 (15th October 2022) - Sung, Min Woo; Driggers, Camden M.; Mostofian, Barmak; Russo, John D.; Patton, Bruce L.; Zuckerman, Daniel M.; Shyng, Show-Ling
Graphical abstract: Highlights: KATP channel activity depends on the interplay of its ligands and its subunits. Inhibitory ligands bias Kir6.2-cytoplasmic domain towards the membrane. SUR1 cooperates with Kir6.2 to stabilize inhibitor ATP and activator PIP2 binding. ATP and PIP2 compete by having overlapping but non-identical binding residues. Ligands shift channel conformational dynamics to regulate channel activity. Abstract: Regulation of pancreatic KATP channels involves orchestrated interactions of their subunits, Kir6.2 and SUR1, and ligands. Previously we reported KATP channel cryo-EM structures in the presence and absence of pharmacological inhibitors and ATP, focusing on the mechanisms by which inhibitors act as pharmacological chaperones of KATP channels (Martin et al., 2019). Here we analyzed the same cryo-EM datasets with a focus on channel conformational dynamics to elucidate structural correlates pertinent to ligand interactions and channel gating. We found pharmacological inhibitors and ATP enrich a channel conformation in which the Kir6.2 cytoplasmic domain is closely associated with the transmembrane domain, while depleting one where the Kir6.2 cytoplasmic domain is extended away into the cytoplasm. This conformational change remodels a network of intra- and inter-subunit interactions as well as the ATP and PIP2 binding pockets. The structures resolved key contacts between the distal N-terminus of Kir6.2 and SUR1′s ABC module involving residues implicated in channel function and showed a SUR1 residue, K134, participates in PIP2 binding. Molecular dynamics simulations revealed two Kir6.2 residues, K39 and R54, that mediate both ATP and PIP2 binding, suggesting a mechanism for competitive gating by ATP and PIP2 .